Synthesis of Nano Crystalline Gamma Alumina from Waste Cans - Ahmedzeki, Nada Sadoon; Hussein, Sattar Jalil; Abdulnabi, Waqar Abdulwahid (Iraqi Journal of Chemical and Petroleum Engineering, 2018)
In the present study waste aluminium cans were recycled and converted to produce alumina catalyst. These cans contain more than 98% aluminum oxide in their structure and were successfully synthesized to produce nano sized gamma alumina under mild conditions. A comprehensive study was carried out in order to examine the effect of several important parameters on maximum yield of alumina that can be produced. These parameters were reactants mole ratios (1.5, 1.5, 2, 3, 4 and 5), sodium hydroxide concentrations (10, 20, 30, 40, 50 and 55%) and weights of aluminum cans (2, 4, 6, 8 and 10 g). The compositions of alumina solution were determined by Atomic absorption spectroscopy (AAS); and maximum yield of alumina solution was 96.3% obtained at 2 mole ratios of reactants, 40% sodium hydroxide concentrations and 10g of aluminum cans respectively. Gamma alumina was acquired by hydrothermal treatment of alumina solution at pH 7 and calcination temperature of 550 ºC. The prepared catalyst was characterized by X-ray diffraction (XRD), N2 adsorption/ desorption isotherms, X-ray fluorescence (XRF) and atomic force microscopy (AFM). Results showed good crystallinity of alumina as described by XRD patterns, with surface area of 311.149 m2/g, 0.36 cm3/g pore volume, 5.248 nm pore size and particle size of 68.56 nm respectively.